2011
DOI: 10.1111/j.1525-1594.2011.01378.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Parameters for Detection of Splanchnic Hypoxia in Children Undergoing Cardiopulmonary Bypass With Pulsatile Versus Nonpulsatile Normothermia or Hypothermia During Congenital Heart Surgeries

Abstract: The aim of this study is to evaluate gastric mucosal oxygenation together with whole-body oxygen changes in infants undergoing congenital heart surgery with cardiopulmonary bypass (CPB) procedure and the use of either pulsatile or nonpulsatile mode of perfusion with normothermia and pulsatile or nonpulsatile moderate hypothermia. Sixty infants undergoing congenital cardiac surgery were randomized into four groups as: nonpulsatile normothermia CPB (NNCPB, n = 15), pulsatile normothermia CPB (PNCPB, n = 15), non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Of the remained 3032 studies were selected by review of title and abstract, 148 studies were retrieved for full text review. Finally, seven RCTs were included according to our prespecified inclusion criteria, enrolling 419 pediatric patients undergoing cardiac surgery from seven countries (Figure ). Study methodological quality is listed (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the remained 3032 studies were selected by review of title and abstract, 148 studies were retrieved for full text review. Finally, seven RCTs were included according to our prespecified inclusion criteria, enrolling 419 pediatric patients undergoing cardiac surgery from seven countries (Figure ). Study methodological quality is listed (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative measures such as total hemodynamic energy (THE) have been used to determine the efficacy of the pump in providing adequate perfusion. Evidence suggests that increased pulsatile perfusion, quantified by surplus hemodynamic energy (SHE), improves patient outcome by minimizing inflammatory response as well as improving vital organ recovery . Using orthogonal polarization spectral imaging, O'Neil et al demonstrated that pulsatile perfusion during CPB was able to better preserve the microcirculation and resulted in less leukocyte activation compared with conventional nonpulsatile perfusion .…”
mentioning
confidence: 99%
“…Not only the quantity, but also the quality of these articles generated by this event based on high‐impact factors (average impact factor is greater than 2.7 annually) are also very impressive. Only during the last 2 years' events, topics covered show the clear evidence of the uniqueness and importance of this conference (Table ) .…”
Section: What Is Unique About This Event?mentioning
confidence: 99%